Business failure research: a review of the Chinese experience. (2015) - Amankwah-Amoah, Joseph; Zhang, Hongxu
In spite of a growing body of literature on business failures in China and the effects of government policy, our understanding of the current state of knowledge remains unclear. The study advances research on the subject by developing the 'four-parties' framework to review and synthesises the literature. The paper lays the groundwork for an integrated understanding of the causes and consequences of business failure. In sharp contrast with the evolution and development of western-based business failure research, much of the literature on China and the Chinese firms have focused largely on business failure prediction models by bypassing the traditional evolution from qualitative case study/story approaches to quantitative-based approaches. The study outlines the important implications and promising avenues for future research.